2020
DOI: 10.1037/pro0000359
|View full text |Cite
|
Sign up to set email alerts
|

The MMPI-2-RF: A pilot study of Latinx vs. non-Latinx Whites profiles.

Abstract: Considering that Latinxs constitute the largest minority group in the United States and that the Spanish language has been noted to be an important consideration when administering psychological tests, an evaluation of this measure with Spanish-speaking Latinxs was warranted. Data was collected from a primary care clinic in a predominately Latinx neighborhood. Participants consisted of 50 Latinx and 30 non-Latinx White (NLW) primary care patients. Participants completed a basic demographic questionnaire that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Among Latinx people, the findings related to the validity of the measure have been mixed. Although there is some evidence that racial/ethnic identity and acculturation are associated with responding on the L and K scales, more recent evidence suggests differential responding on the validity scales alone (Benuto et al, 2020).…”
Section: Summary Of Review Findingsmentioning
confidence: 99%
“…Among Latinx people, the findings related to the validity of the measure have been mixed. Although there is some evidence that racial/ethnic identity and acculturation are associated with responding on the L and K scales, more recent evidence suggests differential responding on the validity scales alone (Benuto et al, 2020).…”
Section: Summary Of Review Findingsmentioning
confidence: 99%
“…Many of these instruments were initially normed on predominantly White male samples, and research conducted on older versions of some assessments has found statistical differences in scores between the norming sample and women, ethnically diverse populations, and individuals with lower levels of acculturation (Perlin & McClain, 2009; Tsai & Pike, 2000; Weiss & Rosenfeld, 2012). More recent research, however, suggests that the differences in scores are generally not substantial enough to be the sole cause for clinical scale elevations and thus may be appropriate for use with some diverse populations (Benuto et al, 2020; Whitman et al, 2018).…”
Section: Pragmatic Practice Suggestionsmentioning
confidence: 99%
“…It was suggested that risk assessment tools validated on a predominantly White sample are not designed to account for culture and different world views (Tamatea, 2017) and the same may be true for the personality measures. For example, on the Minnesota Multiphasic Personality Inventory (Butcher et al, 2001) ethnic minorities appear to score higher compared to Caucasians (Arbisi et al, 2002;Benuto et al, 2020;Butcher et al, 2001). This is problematic as it may disadvantage individuals from ethnic minorities in a way that their level of risk and psychopathologies may be perceived as elevated.…”
Section: Future Directions For Researchmentioning
confidence: 99%